2005
DOI: 10.1194/jlr.m500095-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine-1-phosphate inhibition of placental trophoblast differentiation through a Gi-coupled receptor response

Abstract: The failure of placental trophoblasts to differentiate properly is thought to play an important role in the cause of pregnancy disorders such as preeclampsia. We looked at the effects of the bioactive lipid sphingosine-1-phosphate (S1P) on the differentiation of primary human cytotrophoblasts (CTs) into syncytiotrophoblasts (STs) in culture. We found that S1P inhibited CT differentiation measured by human chorionic gonadotropin (hCG) secretion and the expression of placental alkaline phosphatase but had no eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 40 publications
(62 reference statements)
2
40
0
Order By: Relevance
“…Perhaps uterine-derived sphingolipids attenuate trophoblast advancement into the uterus or regulate differentiation of the trophoblast lineage. Johnstone et al [40] recently demonstrated that S1P inhibited differentiation of primary human cytotrophoblasts into syncytiotrophoblasts through a G i -coupled receptor response, a pathway activated by S1P receptors. Sphingosine kinase 1 was also richly expressed in perivascular tissue surrounding larger maternal vascular canals.…”
Section: Discussionmentioning
confidence: 97%
“…Perhaps uterine-derived sphingolipids attenuate trophoblast advancement into the uterus or regulate differentiation of the trophoblast lineage. Johnstone et al [40] recently demonstrated that S1P inhibited differentiation of primary human cytotrophoblasts into syncytiotrophoblasts through a G i -coupled receptor response, a pathway activated by S1P receptors. Sphingosine kinase 1 was also richly expressed in perivascular tissue surrounding larger maternal vascular canals.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, it has been reported that S1P inhibits cytotrophoblast differentiation and could be involved in the pathogenesis of preeclampsia in humans (47). Furthermore, S1P has been shown to induce a dose-dependent vasoconstriction in human uterine arteries during pregnancy (48).…”
Section: Figure 10mentioning
confidence: 99%
“…Sphingosine-1-phosphate (S1P) is part of a key group of signaling sphingolipids recognized to serve diverse roles in a variety of cellular processes, including apoptosis, migration, differentiation and proliferation in a variety of cell types, including endothelial cells, smooth muscle cells, mesenchymal stem cells and macrophages (8)(9)(10). S1P has been demonstrated to act as a ligand of G-protein-coupled receptors, namely S1P receptors (11).…”
Section: Introductionmentioning
confidence: 99%